Konservasi Kelor (Moringa Oleifera) Mendukung Program Pencegahan Anemia Menuju Generasi Emas Bebas Stunting - Rina Sri Widayati; Sri Kustiyati; Dewi Kartika Sari; Renata Fina Antika Cahyani (WASATHON Jurnal Pengabdian Masyarakat, 2025)
Adolescence is the initial period of preparation for pregnancy, so it is necessary to strive for the best nutrition during adolescence. As we know, nutritional status during adolescence plays a very important role in a woman's preparation for pregnancy because of the high incidence of anemia in adolescents, so efforts for early detection and prevention of anemia in adolescents need to be vigilant. Health education about anemia and adolescent nutrition really needs to be given as initial preparation for teenagers to become mothers-to-be so that in the future the babies born will not experience growth and development problems, especially stunting. Nutritional problems that often occur in young women are lack of nutritional intake which will cause malnutrition, chronic lack of energy, lack of protein energy and anemia can occur. Objective: Increase knowledge and behavior of Aisyiyah cadres towards preventing anemia. Method: This empowerment activity was carried out in the village of Belimbing, Polokarto, Sukoharjo using the method of counseling and empowering cadres to utilize empty land to plant Moringa leaves (Moringa Oleifera). Results: If you look at the results of the pre-test and post-test calculations carried out during the activity, namely the results before the extension and empowerment activities were carried out, it is known that the knowledge obtained in the good category was 25% and after the extension and empowerment activities were carried out it increased to 55%. This empowerment activity succeeded in increasing the knowledge and skills of cadres in Belimbing Village as well as ways to prevent anemia through processed Moringa (Moringa Oleifera) leaf products.